Analisis Kelayakan Usaha dan Nilai Tambah Sayuran Pakcoy (Brassica rapa L.) Hidroponik Kemasan (Studi Kasus CV Spirit Wira Utama Tangerang Selatan) - Firly Reza Resdiana; Wagiono Wagiono; Suhaeni Suhaeni (Jurnal Ilmiah Wahana Pendidikan, 2022)
Pakcoy is a horticultular commodity with high nutrition. This commodity has the potential to increase businessmen. This study aims to determine the cost, revenues, income, feasibility of business, and value-added packages of pakcoy in CV Spirit Wira Utama South Tangerang. This study method used is quantitative. This study uses primary data and secondary data. The primary data was obtained from the result by interview using a questionnaire. The respondents of this study were manager and packaging production staff. Secondary data was obtainde from the Central Agency of Statistics and relevant agencies. The analysis techniques used are costs analysis, revenues, income, R/C Ratio, BEP to analyze the feasibility. And the value-added analysis using the Hayami method. The result showed that the total cost of this study was Rp. 7.397.180, the revenue was Rp. 8.240.000, the income was Rp. 842.820 using 32 installation units, the R/C Ratio was 1,11 showed that the business packaged of pakcoy hydroponic is feasible to work on, production volume BEP 185 kg and price BEP Rp. 35.909/kg. The value-added of packaging pakcoy is Rp. 29.898/kg.